2013
DOI: 10.3103/s1068364x13050104
|View full text |Cite
|
Sign up to set email alerts
|

Transportation of coal concentrates at negative ambient temperatures

Abstract: In the cold season, irregular coal supplies to coke plants are aggravated by the need to heat the coal cars. Thawing of rail cars in garages (enclosures) is the least efficient and most expensive approach. Treatment of the coal concentrates with chemical additives reliably prevents freezing in winter during transit from sup pliers to consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Comparison of results indicates that treatment with 5.0% salt by the proposed third method reduces the freezing point of the coal from to -14.7°C and not at -13.5°C (1 and 2 methods) [7].…”
Section: Results Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of results indicates that treatment with 5.0% salt by the proposed third method reduces the freezing point of the coal from to -14.7°C and not at -13.5°C (1 and 2 methods) [7].…”
Section: Results Of the Studymentioning
confidence: 99%
“…It is found that CaO may expediently be used to prevent freezing if its activity is no less than 85-88% and the ambient temperature is not below -(15-16) °C [7]. At lower temperatures, freezing is not prevented by unslaked lime even in quantities of 3-6% of the mass of coal.…”
Section: Results Of the Studymentioning
confidence: 99%
“…The study used an organosilicon fluid GKZh-94, which is a colorless slightly yellow liquid. Density -0,996-1,003 g/cm 3 ; freezing temperature -50 °C; pH not less than 6. In water it is insoluble, but well forms an emulsion, corrosion inactive, does not emit harmful vapors and gases, weatherproof.…”
Section: Fig1 Orientation Of Organosilicon Bonds and Hydrocarbon Ramentioning
confidence: 99%
“…For example, the biomass in a natural state has a high humidity, which reaches to 30.4-79.7% [8], what leads to a low calorific value in terms of the operating state. In addition, such a high humidity of biomass leads to its caking, sticking during a transportation, and in winterto freezing, what additionally complicates the process of transportation and unloading of raw materials [9]. Some types of biomass (for example, bran) are prone to slagging of heating surfaces during combustion [10], as a result of which the service life of the fuel-burning equipment is reduced and the cost of repair works is increased.…”
Section: Introductionmentioning
confidence: 99%